Treynor, Sharpe, and Jensen Ratio of Health Sector Companies on The Indonesia Stock Exchange Before and During Covid-19 Pandemic Period - Dewi Tamara; Ashuri Ashuri; Satria Katon Bagaskara; Sulhadi Sulhadi (Ridwan Institute, 2021)
This research aims to compare the return and risk in investment at the stock portfolio of Health Sector Companies in period before the COVID-19 pandemic and during the COVID-19 pandemic in Indonesia. This research conducted using quantitative method with descriptive approach with secondary data with samples of the stock of Health Sector Companies listed in the Indonesia Stock Exchange (